Evaluating the impact of the graduate fellowship programme of the International Livestock Research Institute. A tools and process report - Eley, R.; Ibrahim, H.; Hambly Odame, Helen; Demeke, M.; Smalley, M.E. (International Livestock Research Institute, 2002)
Post graduate research projects are an effective method for building new research capacity in sub-Saharan Africa. The International Livestock Research Institute (ILRI) offers a graduate fellowship programme for scientists from developing and developed countries. This is done in partnership with universities in African and Asian countries, Europe, Australia and North America. To date such programmes have not been adequately assessed to find the impact on national research capacity, the graduate fellows and the partner institutions. To assess the value of this training, ILRI conducted an impact study of its graduate fellows in Kenya and Ethiopia between 1978 and 1997. This report presents the tools and methods used in this study. Others may use these freely, but appropriate acknowledgement of the source will be appreciated. Future users may modify these instruments for their own impact studies; and indeed are encouraged to do so. We recognise that many improvements could be made and request feedback from others on how they have accomplished this. This report also presents part of the results to enable those interested in future impact studies in Ethiopia or Kenya to use the data as a benchmark.